Advancing Social Research Relationships in Postnatal Support Settings. Issue 3 (12th March 2013) - Tighe, Maria; Peters, Jane; Skirton, Heather
Abstract Global trends in public health nursing (PHN) suggest the value of community‐based social research. However, it is not always clear how social research relationships may be of benefit to PHN or how such skills can best be learned and applied. To advance this understanding, we present a qualitative analysis of the development of social research relationships in PHN. Using a background literature review as a foundation, our qualitative mixed method strategy involved a comparative case‐study analysis based on the authors' participant observation in two distinct postnatal group settings. Our findings suggest that participant observation facilitates the advancement of social research relationships through practitioner‐research management of role conflict. Reflexivity and reciprocity is an emergent relational process, which relies upon a de‐professionalization of the traditional PHN role. Conversely, social research relationships help build PHN capacity for family health needs assessment. Thus, we contend that the application of participant observation enables the development of social research relationships, which advance the practice of PHN in postnatal support settings.